How to depolymerize polymers into reusable raw materials
The use of iron oxide nanoparticles and bases in the decomposition of telephthalate polymers addresses the challenges of high-purity monomer production and catalyst recovery, enhancing conversion rates and separation efficiency in polymer recycling processes.
Patent Information
- Application Number
- JP2024542051
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-17
- Filing Date
- 2023-01-12
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for recycling telephthalate polymers, such as PET, face challenges in achieving high-purity monomers and efficient catalyst recovery, which is crucial for their reuse in industries like food and medical applications, while also requiring improved separation and recovery of catalysts from reaction mixtures.
A method involving the use of nanoparticles as catalysts, specifically iron oxide nanoparticles, in combination with a base, to break down telephthalate polymers into monomers and oligomers, followed by phase separation using centrifugal or magnetic separation techniques, optimizing the reaction conditions and catalyst recovery.
This approach enhances the conversion rate of telephthalate polymers to monomers, improves reaction time and selectivity, and facilitates efficient separation and reuse of catalysts, reducing impurities and health risks associated with cobalt catalysts.
Smart Images

Figure 2025502279000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalytic method for depolymerizing polymers into reusable raw materials, such as terephthalate monomers and oligomers. The present invention further relates to the recovery of the catalyst from the reaction mixture. The present invention also relates to the use of a base as a cocatalyst in the catalytic depolymerization reaction. [Background technology]
[0002] Currently, depolymerization of polymers into reusable raw materials is an area of high interest in industry. One example of a group of polymers that can be recycled is terephthalate polymers, which are a group of polyesters that contain terephthalate in the backbone. The most common example of a terephthalate polymer is polyethylene terephthalate, also known as PET. Other examples include polybutylene terephthalate, polypropylene terephthalate, polyethylene isophthalate, polypentaerythrityl terephthalate, and copolymers thereof, such as copolymers of ethylene terephthalate and polyglycols, such as polyoxyethylene glycol and poly(tetramethylene glycol) copolymers. PET is one of the most common polymers, and there is a strong desire to recycle it by depolymerization into reusable raw materials.
[0003] One of the preferred methods of depolymerization is glycolysis, which is preferably catalytic. Typically, by using an alcohol such as ethylene glycol, a reaction mixture may be formed that contains at least one monomer, including bis(2-hydroxyethyl) terephthalate (BHET). One example of a suitable depolymerization by glycolysis is known from WO 2016 / 105200 in the name of the applicant. According to this method, the terephthalate polymer is depolymerized by glycolysis in the presence of a catalyst. At the end of the depolymerization process, water is added and a phase separation occurs. This makes it possible to separate the first phase, which contains the BHET monomer, from the second phase, which contains the catalyst, oligomers and additives. The first phase may contain impurities in dissolved form and as dispersed particles. The BHET monomer can be obtained in pure form by crystallization.
[0004] The reuse of depolymerized raw materials requires high purity. As is well known, contaminants can affect the subsequent polymerization reaction from the raw materials. Furthermore, terephthalate polymers are also used in food and medical applications, so strict regulations are applied to prevent health problems.
[0005] The Applicant's process according to WO 2016 / 105200 allows for a very high conversion of the terephthalate polymer and also facilitates the separation of the various additives from the BHET monomer, but also allows for a further optimization of the depolymerization reaction, and further improves the recovery of the catalyst from the reaction mixture. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 105200 [Patent Document 2] International Publication No. 2017 / 111602 [Patent Document 3] International Publication No. 2015056377A1 Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, there is a need to provide a method for depolymerizing polymers into pure, reusable raw materials suitable for the preparation of new polymers. An example of a polymer is a terephthalate polymer. In such a method, the conversion of the polymer is not always very high, but an acceptable conversion can be achieved. To improve the conversion, catalysts are used. These catalysts are separated from the monomers and reused after separation. The object of the present invention is to further improve the catalytic depolymerization method and to further improve the separation and recovery of the catalyst. [Means for solving the problem]
[0008] According to a first aspect of the present invention, there is provided a method for obtaining a monomer by degrading a polymer, the polymer being a homopolymer or copolymer of a monomer, the method comprising the steps of: a. feeding a polymer and a solvent into a reactor as a reaction mixture, the solvent being a reactant capable of reacting with the polymer to break it down into oligomers and at least one monomer; b. providing a reusable catalyst capable of degrading the polymer into oligomers and at least one monomer; c. decomposing the polymer in the reaction mixture under reaction conditions using the catalyst to form at least one monomer; and d. recovering the catalyst from the reaction mixture; and in at least one of the reaction steps a to d, further comprising adding at least one base to the reaction mixture.
[0009] According to a second aspect of the present invention, the present invention further relates to the use of a base as a co-catalyst for a catalyst which degrades a polymer in a reaction mixture under reaction conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The terminology used in the present specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the present invention.
[0011] The present invention is a method for obtaining monomers by decomposing a polymer, the polymer being a homopolymer or copolymer of a monomer. A reusable catalyst capable of decomposing the polymer into oligomers and at least one monomer is used. In order to recover the catalyst more easily and in greater quantities, at least one base is added to the reaction mixture in at least one of the reaction steps a-d. Furthermore, it has been established that a base improves the catalytic decomposition of the polymer into smaller molecules (catalytic decomposition) when added to the reaction mixture during or before step c. The reaction time and selectivity are improved.
[0012] The polymer and the solvent are fed into the reactor as a reaction mixture, the solvent being a reactant capable of reacting with the polymer to break it down into oligomers and at least one monomer. The depolymerization of polyesters more preferably occurs by solvolysis, the solvent acting as a reactant. Typical solvents are alkanols and alkanediols, such as ethylene glycol, methanol, diethylene glycol, propylene glycol, dipropylene glycol. Ethylene glycol has been found to be suitable in view of its physical properties (such as a boiling point of about 200° C.). In the depolymerization of PET, the use of ethylene glycol results in bis(2-hydroxyethyl) terephthalate (BHET) as the main depolymerization product. Dimers, trimers and further oligomers are also obtained. BHET and its dimers can be purified and obtained in sufficient purity by crystallization. One way is to process the aqueous phase obtained after adding water and / or an aqueous solution to a vessel downstream of the process and separate it from the second phase in a centrifuge, as described above. Examples of this are identified in the above-mentioned International Publication No. WO 2017 / 111602, which is incorporated herein by reference.
[0013] Advantageously, the weight ratio of the solvent, preferably ethylene glycol, to the polymer ranges from 10:10 to 100:10, more preferably from 20:10 to 90:10, most preferably from 40:10 to 60:10.
[0014] In a preferred embodiment of the invention, the polymer concentration in the dispersion is from 1 to 30% by weight of the total weight of the reaction mixture.
[0015] A reusable catalyst capable of decomposing the polymer into oligomers and at least one monomer is provided to the reaction mixture. The present invention can be carried out using any catalyst suitable for this purpose.
[0016] In the depolymerization process according to one embodiment, during step c, the catalyst forms a dispersion in the reaction mixture.
[0017] In recent years, nanoparticles have attracted attention as depolymerization catalysts. Since the diffusion rate in liquids is several orders of magnitude smaller than that in gases, small particles are required for reactions in the liquid phase. Such nanoparticles have small diameters and surface areas of 0.5 to 200 m2. 2 / g range. It is believed that nanoparticles are highly active, resulting in faster depolymerization, thereby making the process economically viable. To separate such nanoparticles, several options are available. Some of the possible depolymerization catalysts are based on ferromagnetic and / or ferrimagnetic materials. Also, antiferromagnetic, synthetic magnetic, paramagnetic, superparamagnetic materials, such as materials containing at least one of Fe, Co, Ni, Gd, Dy, Mn, Nd, Sm, and preferably materials containing at least one of O, B, C, N, such as iron oxides, such as ferrites, such as magnetite, hematite, and maghemite, can be used. The use of magnetic materials allows separation mainly by magnetic forces, but many nanoparticles are very small and may not be attracted to themselves sufficiently. However, when a magnetic field is applied, the nanoparticles can form magnetic clusters, which are more easily separated by magnetic forces. In both magnetic and non-magnetic nanoparticle catalysts, clusters of nanoparticles with larger sizes can also be generated by adding other compounds. The present invention provides an improved solution.
[0018] One type of suitable catalyst includes transition metals in metallic or ionic form. Ionic form includes free ions in solution and in ionic or covalent bonds. Ionic bonds are formed when one atom donates one or more electrons to another atom. Covalent bonds are formed by interatomic bonds resulting from the sharing of electron pairs between two atoms. The transition metal may be selected from the first transition metals, also known as 3d orbital transition metals. More specifically, the transition metal is selected from iron, nickel, and cobalt. However, iron and nickel particles are most preferred, since cobalt is hazardous to health and iron and nickel particles can be formed in pure form. Additionally, alloys of the individual transition metals may be used.
[0019] The nanoparticles are preferably magnetic, either containing a magnetic material or capable of being sufficiently magnetized under a relatively gentle magnetic field as applied in the method. Preferably, the magnetic nanoparticles contain iron, nickel and / or cobalt in oxidized or metallic form, or a combination thereof. Iron oxide is preferably in the form of, for example but not limited to, Fe3O4. Another suitable example is Fe2O3. A suitable example from an alloy is CoFe2O4. Other suitable examples are NiFe2O4, Ni2Fe2O5, or NiO.
[0020] If the nanoparticles are made of metal, they may be provided with an oxide surface, which can further enhance catalytic activity. The oxide surface may form by itself on contact with air or water, or the oxide surface may be applied intentionally.
[0021] It has been found that the nanoparticles must be small enough so that the catalytic complex acts as a catalyst for breaking down the polymer into smaller units, in which case the yield of the smaller units of the polymer, in particular its monomers, is high enough for commercial reasons. Furthermore, it has been found that the nanoparticles must be large enough to allow the catalyst to be reused by recovery. It is economically undesirable for the catalyst to be removed either with the waste or with the resulting decomposition products. Suitable nanoparticles have an average diameter in the range of 2 to 500 nm, more preferably in the range of 3 to 200 nm, even more preferably in the range of 4 to 100 nm. From the standpoint of yield and recovery of the catalytic complex, it has been found that particles of a fairly small size, for example 5 to 10 nm, are optimal. It should be noted that the term "size" refers to the average diameter of the particles, and that the actual diameter of the particles may vary somewhat depending on their characteristics. Furthermore, aggregates may form, for example in the solution. These aggregates typically have a size in the range of 50 to 200 nm, for example 80 to 150 nm, for example a size of about 100 nm. It is preferred to use nanoparticles containing iron oxide.
[0022] Particle size and its distribution can be measured by light scattering using a Malvern dynamic light scattering instrument, such as the NS500 series. A more laborious method, typically applied to small particle sizes but equally applicable to larger sizes, involves taking a representative electron micrograph and measuring the size of individual particles on the photograph. For the average particle size, a number mass average can be taken. As a rough estimate, the average can be taken as the size with the most number of particles, or the median size.
[0023] Most preferred is the use of iron or iron-containing particles. Not only are iron and iron-containing particles magnetic, but they have been found to catalyze the depolymerization of PET to, for example, 70-90% conversion to monomer within an acceptable reaction time of up to 6 hours, depending on other process factors such as catalyst loading and PET / solvent ratio. The catalyst concentration required is 1% by weight or less relative to the amount of PET. Good results have been obtained with catalyst loadings of less than 0.2% or even less than 0.1% by weight relative to the amount of PET. Such low catalyst loadings are highly beneficial and allow the method of the present invention to recover increased amounts of nanoparticle catalyst.
[0024] Non-porous metal particles, particularly transition metal particles, may be suitably prepared by thermal decomposition of carbonyl complexes, such as iron pentacarbonyl and nickel tetracarbonyl. Alternatively, iron and nickel oxides may be prepared by exposing the metals to oxygen at high temperatures, such as 400° C. or higher. Non-porous particles may be more suitable than porous particles, since the particles may be less exposed to alcohol, and therefore less corroded, allowing the particles to be reused for catalysis more frequently. Furthermore, the limited surface area may result in fewer metal ions due to oxidation at the surface, and therefore lower levels of ions present in the product stream as contaminants to be removed.
[0025] The non-porous particles according to the invention preferably have a surface area of 10 m 2 / g, more preferably at most 5m 2 / g, and even more preferably at most 1 m 2 / g. The porosity is preferably 10 -2 cm 3 / g or, for example, at most 10 -3 cm 3 / g.
[0026] Another class of suitable catalysts includes nanoparticles based on alkaline earth elements selected from beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba) and their oxides. A preferred alkaline earth metal oxide is magnesium oxide (MgO). Other suitable metals include, but are not limited to, titanium (Ti), zirconium (Zr), manganese (Mn), zinc (Zn), aluminum (Al), germanium (Ge), and antimony (Sb), and their oxides and further alloys. Also suitable are noble metals such as palladium (Pd) and platinum (Pt). MgO and ZnO have been found to catalyze the depolymerization of PET to monomer conversion, for example, 70-90%, within an acceptable reaction time, depending on other process factors such as catalyst loading and PET / solvent ratio. Also suitable catalysts based on hydrotalcite are contemplated.
[0027] Preferably, the nanoparticles are selected to be substantially insoluble in the (alcoholic) reactive solvent, even at elevated temperatures above 100° C. Less suitable are oxides such as amorphous SiO2, which tend to dissolve readily at elevated temperatures in alcohols such as ethylene glycol.
[0028] Suitable catalysts according to the invention may be coated. For example, Fe3O4 particles may be coated with a material to protect the particles from oxidation to Fe2O3 with different magnetic properties. Thus, the surface of the catalyst particles may be coated with a material such as polyethyleneimine (PEI), polyethylene glycol (PEG), silicone oil, fatty acids such as oleic acid or stearic acid, silane, mineral oil, amino acids, or polyacrylic acid, or polyvinylpyrrolidone (PVP). Carbon is also a possible coating material.
[0029] The coating may be removed prior to or during the catalytic reaction, for example by using a separate solvent washing step or by burning in air prior to use in the reactor.
[0030] Particularly preferred catalysts relate to catalytic complexes (ABC), which comprise three identifiable elements: (nano)particles (A), bridging moieties / binding groups (B) that are chemically bound to the particle, such as by covalent bonds, or physically, such as by adsorption, and catalytic entities (C) that are bound to the particle (A) by chemical bonds, such as covalent bonds. The binding groups preferably do not completely cover the nanoparticle surface, as in core-shell particles. The nanoparticles of this catalytic complex are preferably based on ferromagnetic and / or ferrimagnetic materials. Also, antiferromagnetic materials, synthetic magnetic materials, paramagnetic materials, superparamagnetic materials, such as materials containing at least one of Fe, Co, Ni, Gd, Dy, Mn, Nd, Sm, and preferably materials containing at least one of O, B, C, N, such as iron oxides, such as ferrites, such as magnetite, hematite, and maghemite, can be used. From a cost perspective, relatively inexpensive particles, such as iron-containing particles, are preferred, even when the catalytic complex is fully or largely recovered. An additional advantage of iron or iron oxide particles is that they have the highest saturation magnetization, making them easier to separate through a magnetic separator. Even more importantly, iron oxide nanoparticles have a positive effect on the decomposition reaction. The iron oxide may further contain additional elements, such as cobalt and / or manganese, e.g., CoFe2O4.
[0031] Preferably, the nanoparticles are selected to be substantially insoluble in the (alcoholic) reactive solvent, even at elevated temperatures above 100° C. Less suitable are oxides such as amorphous SiO2, which tend to dissolve readily in alcohols such as ethylene glycol at elevated temperatures.
[0032] The functional groups of the crosslinking moieties are, for example, weak organic acids such as carboxylic acids or dicarboxylic acids, but preferably silanols such as silanediols and silanetriols. The crosslinking moieties may be introduced as reactants in the form of silyl-containing groups such as silyl ethers, e.g., triethoxysilylpropyl halide. The linking group may be, for example, an alkylene chain, where the alkylene is typically from C2 to C6. 10Between C3 and C5, preferably propylene, butylene, pentylene. Propylene is preferred. The bridging moiety is preferably provided as a reactant, where the linking group is functionalized for chemical reaction with the catalytic entity, while the functional group is protected. For example, a suitable functionalization of the linking group is to provide it as a substituted alkyl halide. A suitable protection of the functional group may be in the form of an ester or alkoxysilane. The alkoxy group is preferably ethoxy, but methoxy or propoxy are not excluded.
[0033] In a further embodiment, the alkoxysilane is provided as a trialkoxysilane with one alkylene group constituting the linking group. In another embodiment, a dialkyl-dialkoxysilane is used in which one of the alkyl groups is the linking group. In yet another embodiment, a monoalkoxy-trialkylsilane is used in which one of the alkyl groups is the linking group. In the latter case, the alkyl groups are preferably lower alkyls such as C1-C4 alkyls, thus methyl, ethyl, propyl, n-butyl, isobutyl. At least one of the alkyls is then functionalized, for example with a halide, as defined above. Linear alkyls are considered to be preferred to limit steric hindrance.
[0034] It is understood that the use of dialkyl-dialkoxysilanes and / or monoalkoxy-trialkylsilanes results in better separation between the hydrophilic solution and the second phase in one embodiment, and is beneficial in one embodiment using phase separation to ensure that the complex enters the second phase rather than the hydrophilic solution where it would be lost. It is believed that not all alkoxy groups of the trialkoxysilanes are bound to the surface of the nanoparticle aggregates. Some alkoxy groups may remain protected. However, the addition of water to the complex may remove the protecting groups. This may result in increased hydrophilicity of the complex. By using silanes with fewer alkoxy groups, the remaining groups are essentially non-polar and do not become deprotected. Thus, the overall complex becomes more hydrophobic. Not only one type of bridging moiety, also known as a silane coupling agent, but mixtures thereof, such as a mixture of alkyltrialkoxysilanes and dialkyl-dialkoxysilanes, may be used, where one of the alkyl groups is functionalized as a halide to react with the catalytic entity and then carries the catalytic entity after both reactions. The addition of dialkyldialkoxysilanes can effectively reduce the size of the layer of groups attached to the surface, which is not considered a disadvantage.
[0035] The moiety may be aromatic, aliphatic or heterocyclic. The aromatic heterocyclic moiety suitably comprises a heterocycle having at least one, preferably at least two, nitrogen atoms. The heterocycle may have 5 or 6 atoms, preferably 5 atoms. Suitable aromatic heterocycles are pyrimidine, imidazole, piperidine, pyridine, pyrazole, oxazole, triazole, thiazole, methimazole, benzotriazole, isoquinol and viologen-based compounds (e.g., having two linked pyridine ring structures). Particularly preferred are imidazole structures which generate imidazolium ions. The negatively charged moiety may be associated with an anionic complex, or alternatively with a simple ion such as a halide. Preferably, the reaction of the alkyl halide of the bridging moiety with an uncharged aromatic heterocyclic moiety containing at least one nitrogen atom generates a positive charge on the aromatic moiety, particularly the nitrogen atom therein, and generates a negative halide. The negatively charged halide can then be enhanced by the addition of a Lewis acid to form a metal salt complex. An example is the chloride (chloride ion) FeCl4 - The aromatic moiety, in one example, has at least one tail. The at least one tail is preferably C1-C 10 The tail may have a length of, for example, C2-C4, with at least one tail preferably being attached to a nitrogen atom, more specifically the tail that extends into the carrier liquid and away from the crosslinking moiety. Longer tails are considered beneficial in increasing the hydrophobicity of the complex, thereby reducing the tendency of the complex to enter the hydrophilic phase.
[0036] According to the present invention, the bridging moiety and the catalytic entity attached thereto are 5×10 -6 ~0.1, preferably 1×10 -5 ~0.01, more preferably 2×10 -5 ~10 -3 , for example 4×10 -5 ~10 -4(moles of crosslinked moieties / g of magnetic particles). From the standpoint of efficient selective recovery of the catalytic complex, it is preferred to have relatively large amounts available, but from the standpoint of catalyst quantity and cost, somewhat smaller amounts may be more preferred.
[0037] It has been found that limited surface coverage of the nanoparticles or aggregates of such particles with catalytic groups is sufficient to provide an effective catalyst. When a given amount (mol) of bridging moieties are attached to a given amount (g), it is assumed that substantially all of the bridging moieties are attached to the nanoparticles and remain substantially attached during the process.
[0038] In step c of the process, decomposition of the polymer takes place in the reaction mixture at reaction conditions using a catalyst to form monomers. The reaction mixture is preferably heated to a suitable temperature, which is preferably maintained during the depolymerization. The temperature may be selected in the range of 170° C. to 250° C. In a preferred embodiment, the decomposition step may comprise forming monomers at a temperature in the range of 185° C. to 225° C. The preferred pressure in the reactor is 1 to 5 bar, with a pressure higher than 1.0 bar being preferred, more preferably lower than 3.0 bar.
[0039] The catalyst can be largely recovered if it is not dissolved in the solvent and is to a heterogeneous extent. In step d, the catalyst is recovered from the reaction mixture. Separation is carried out, for example, by centrifugation. The presence of agglomerates is considered to be advantageous, since it can make the phase separation more effective.
[0040] The method further comprises the addition of at least one base in at least one of the reaction steps a, b, c or d. The effect of the addition of the base is to improve the decomposition reaction of the polymer into oligomers and monomers by shortening the reaction time and / or reducing the formation of by-products. The base can be added in step a together with the polymer or the solvent or separately. Depending on the nature of the base, the base can be added as a solid or dissolved in water or a solvent. When a non-volatile base is used, it is preferred to add the base in solid form or at least partially dissolved in the solvent already used in step a of the method. When a volatile base is added, it is preferably dissolved in water or the solvent of the reaction mixture. The base can also be added in step b of the method together with the reusable catalyst or separately. The base can further be added in step c of the method before or during the decomposition of the polymer in the reaction mixture.
[0041] The base can also be added in step d of the process before or during recovery of the catalyst from the reaction mixture. The base has an effect on the separation of the catalyst from the reaction mixture. The separation is improved and the catalyst is more easily recovered.
[0042] The amount of base and the amount of catalyst added to the reaction mixture ranges from 0.1:1 to 40:1, more preferably from 1:1 to 35:1, and most preferably from 2:1 to 5:1.
[0043] Advantageously, water is added to the reaction mixture before or during recovery of the catalyst. Water can be added separately or together with the base. The step of adding water, with or without a base, to the reaction mixture results in a first aqueous phase containing monomers and dimers and a second phase containing oligomers, catalyst complexes and aggregates, and separation of the first phase from the second phase. This has been found to be an effective method of removing various contaminants. In a preferred implementation herein, the second phase is treated to reduce the water content and then recycled to the reaction vessel. Reduction of the water content can be done in various ways, for example by evaporation, such as distillation and / or membrane distillation.
[0044] The recovery step according to the present method preferably comprises a step of separating the catalyst from the reaction mixture. The separation step is more preferably carried out using a centrifuge. Alternatively, the separation step is preferably carried out using magnetic separation and / or application of an electric field. In a preferred embodiment where water is added to the reaction mixture, the separation is preferably carried out at a temperature between 60° C. and 100° C., more preferably between 75° C. and 95° C. If water is not present, the separation may be carried out at a higher temperature.
[0045] Advantageously, the water or aqueous solution added to the reaction mixture before or during the recovery of the catalyst can act as a coolant. It may be provided at room temperature or at any higher temperature, preferably liquid. Nevertheless, it is not excluded to provide a separate cooling means. Upon addition of water or aqueous solution, two phases appear, of which the first is an aqueous phase containing the solvent, monomers and at least some dimers and trimers. The second phase is a slurry containing various solids such as catalyst, oligomers, trimers and solvent.
[0046] The water added to the reaction mixture in step d is preferably in an amount such that the mass ratio of water to solvent is in the range of 0.2 to 5.0, more preferably 0.5 to 1.5, even more preferably 0.7 to 1.3, and most preferably 0.9 to 1.1. Usually, the more water added, the more catalyst and oligomer precipitation occurs. However, this also generally means that more water needs to be distilled in order to separate or recycle the catalyst and oligomers.
[0047] In preferred embodiments where both base and water are added, the weight ratio of base to water ranges from 0.01 to 1.0, more preferably from 0.05 to 0.5, and most preferably from 0.08 to 0.12. Preferably, water and / or base are added in an amount to raise the pH of the reaction mixture above 6.
[0048] The amount of catalyst relative to the amount of polymer is fairly small, preferably in the range of 0.001:10 to 1:10, more preferably 0.005:10 to 0.3:10, and most preferably 0.008 to 0.015:10.
[0049] The base added to at least one of the reaction steps is preferably a volatile base, including aqueous solutions of ammonia and / or trialkylamines.Suitable amine-containing compounds are disclosed, for example, in WO2015056377A1, which is expressly incorporated herein by reference insofar as the amine-containing compounds described therein are concerned.The use of a volatile base is advantageous, since the aqueous phase is recycled and little or no elemental contamination of the product is observed.
[0050] In another embodiment, the base added to the reaction mixture before or during recovery of the catalyst is preferably a non-volatile base, including metal hydroxides, more preferably lithium hydroxide (LiOH), sodium hydroxide (NaOH), potassium hydroxide (KOH), rubidium hydroxide (RbOH), cesium hydroxide (CsOH), magnesium hydroxide (Mg(OH)), calcium hydroxide (Ca(OH)), strontium hydroxide (Sr(OH)), barium hydroxide (Ba(OH)), tetramethylammonium hydroxide (N(CH3)4OH), potassium tert-butoxide, sodium bicarbonate, and guanidine (HNC(NH2)2).
[0051] When the base is a non-volatile base, including a metal hydroxide, the base is preferably added in step a or step b of the process. In addition, a non-volatile or volatile base can be further added in step d of the process to improve the recovery of the catalyst from the reaction mixture. Thus, the base can be the same base or the base added in step d can be a volatile base. The base added in step a or b acts as a co-catalyst for the depolymerization reaction. The presence of the base increases the rate of depolymerization and also suppresses the formation of by-products.
[0052] According to another embodiment of the invention, the recovery step d is preferably carried out immediately after the addition of water and / or base.
[0053] In one embodiment of the present invention, the addition of water and base to the reaction mixture before or during recovery of the catalyst in step d is carried out at a temperature below 160° C., preferably below 100° C. For optimal agglomerate formation and oligomer precipitation, it is advantageous to carry out this addition at low temperature.
[0054] Advantageously, after the decomposition step, the reaction mixture is cooled to below 170° C. before the step of adding water and / or base. The water is preferably at a temperature of at least 85° C.
[0055] The present invention is further directed to the use of the above-mentioned bases as cocatalysts for catalysts that degrade polymers in a reaction mixture, the bases being active in this reaction and preferably remaining in the system, which can affect both the depolymerization reaction and the recovery of the catalyst.
[0056] For example, NaOH was found to be a promising cocatalyst because the addition of NaOH increased the activity of the depolymerization catalyst in the depolymerization reaction while leaving the formation of, for example, BHEET unchanged. Also, the separation property of the catalyst was improved by adding NaOH.
[0057] During depolymerization, it can be important to avoid producing too much BHEET in the reactor. BHEET is defined by Formula I below.
[0058] [ka]
[0059] It has been found that the presently claimed catalyst, i.e. a reusable catalytic complex capable of degrading polymers into oligomers and / or monomers, preferably comprising catalytic entities, metal-containing particles, and bridging moieties for connecting the catalytic entities to magnetic particles, and a base, produces reduced amounts of BHET at the same BHET yield when compared to other catalysts.
[0060] These and other advantages of the features and objects of the present invention will become more apparent and the invention will be better understood from the following detailed description when read in conjunction with the accompanying drawings. [Brief description of the drawings]
[0061] [Figure 1] FIG. 1 is a graph showing the separation efficiency of catalysts with various base additions. [Diagram 2] FIG. 2 is a graph showing the yield of BHET as a result of Test 11. [Diagram 3] FIG. 3 is a graph showing the formation of the by-product BHEET. [Figure 4] FIG. 4 is a graph showing the separation efficiency of the ABC catalyst complex with the addition of other bases. [Diagram 5] FIG. 5 is a graph showing the separation efficiency of the ABC catalyst complex with the addition of a particular base.
[0062] The following non-limiting examples are provided to illustrate the present invention. EXAMPLES
[0063] test <Comparative Test A: Separation Efficiency - Catalyst ABC> The separation test was carried out using a 600 ml flask. A quantity of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). To the reaction mixture, 125 g of ethylene glycol (EG) and 125 g of water were added.
[0064] The flask was heated to 80-100°C and mixed at that temperature to ensure dissolution of the BHET. The depolymerized mixture was transferred to a 50 mL centrifuge tube. The mixture was centrifuged at 4000 rpm for 3 minutes. The supernatant was separated by decantation and then cooled to crystallize the BHET product present in the supernatant. The BHET crystals were filtered from the mother liquor using a Buchner filter and dried in a vacuum oven at 60°C. The dried BHET and mother liquor were then analyzed by XRF to estimate the separation of the catalyst from the mixture. The separation efficiency as % of the catalyst present is shown in Figure 1.
[0065] <Example 1: Separation efficiency - catalyst ABC + ammonia> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.125 g of 28% ammonia solution was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0066] <Example 2: Separation efficiency - Catalyst ABC + NaOH> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.05 g of sodium hydroxide was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0067] <Example 3: Separation efficiency - Catalyst ABC + LiOH> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.1 g of lithium hydroxide was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0068] <Example 4: Separation efficiency - Catalyst ABC + Na2CO3> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.5 g of sodium carbonate was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0069] <Example 5: Separation efficiency - Catalyst ABC + triethylamine (TEA)> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.5 g of triethylamine was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0070] <Example 6: Separation efficiency - Catalyst ABC + Tripropylamine (TPA)> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.05 g of tripropylamine was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0071] <Example 7: Separation efficiency - catalyst ABC + 1-methylimidazole (NMI)> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.05 g of 1-methylimidazole was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of the catalyst present is shown in Figure 1.
[0072] <Example 8: Separation efficiency - Catalyst ABC + N"-Pentamethyldiethylenetriamine (PMDETA)> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of iron-based ABC catalyst complex was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.5 g of N″-pentamethyldiethylenetriamine was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of catalyst present is shown in Figure 1.
[0073] Comparative test B: Separation efficiency - Fe3O4 The separation test was carried out using a 600 ml flask. An amount of 0.017 g of Fe3O4 was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a percentage of the catalyst is shown in Figure 1.
[0074] <Example 9: Separation efficiency - Fe3O4+NaOH> The separation test was carried out using a 600 ml flask. An amount of 0.017 g of Fe3O4 was used in combination with 16.7 g of bis(2-hydroxyethyl) terephthalate (BHET). 125 g of ethylene glycol (EG) and 125 g of water were added to the reaction mixture. 0.05 g of sodium hydroxide was added to the mixture. The same depolymerization reaction procedure as described in Comparative Test A was used. The separation efficiency as a % of the catalyst present is shown in Figure 1.
[0075] <Example 10: Depolymerization reaction> The depolymerization test was carried out using a 500 ml round bottom flask. 0.034 g of the iron-based ABC catalyst complex, or 0.05 g of NaOH, or a combination of these, was added to polyethylene terephthalate (PET) flakes (0.3 × 0.3 cm 2 A 100 g reaction mixture was used with 33.4 g of bis(2-hydroxyethyl) terephthalate, or BHET, and 250 g of ethylene glycol. The round-bottom flask was placed in a heating apparatus. Heating was started, and after 20 minutes, the reaction mixture reached a reaction temperature of 197° C. The reaction was followed by in-process control samples taken at regular intervals to measure the concentration of the monomer (bis(2-hydroxyethyl) terephthalate, or BHET) and by-product (e.g., 2-(2-hydroxyethoxy)ethyl (2-hydroxyethyl) terephthalate, or BHEET) produced as a function of time. The concentrations of BHET and BHEET were measured by HPLC.
[0076] The results are shown in Figures 2 and 3. In Figure 2, the yield of BHET as a function of reaction time is shown for different catalyst systems. ABC catalyst with NaOH as promoter gives faster conversion of polymer to BHET. In Figure 3, the formation of the by-product BHEET as a function of reaction time is shown for different catalyst systems. The formation of BHEET is clearly suppressed by the presence of NaOH as promoter.
[0077] <Comparative Example C: Separation Efficiency - Catalyst ABC> The same depolymerization reaction procedure was used as described in Example 10, using 0.034 g of iron-based ABC catalyst complex. After 240 min at 197° C., the reaction was stopped by cooling to below 160° C. The reaction mixture was transferred to a beaker through a sieve filter to remove remaining solids. Water was added to obtain a 1:1 water:EG ratio. The mixture was mixed. A pre-centrifugation sample was taken. The mixture was transferred to a centrifuge tube and centrifuged at 4000 rpm for 3 min. A post-centrifugation sample was taken. The sample was analyzed by XRF to estimate the separability. The results are shown in Figure 4.
[0078] <Example 11: Separation efficiency - catalyst ABC + NaOH and water> The same depolymerization reaction procedure was used as described in Example 10, using 0.034 g of iron-based ABC catalyst complex and 0.05 NaOH. After 240 min at 197° C., the reaction was stopped by cooling to below 160° C. The reaction mixture was transferred to a beaker through a sieve filter to remove remaining solids. Water was added to obtain a 1:1 water:EG ratio. The mixture was mixed. A pre-centrifugation sample was taken. The mixture was transferred to a centrifuge tube and centrifuged at 4000 rpm for 3 min. A post-centrifugation sample was taken. The sample was analyzed by XRF to estimate the separability. The results are shown in Figure 4.
[0079] <Example 12: Separation efficiency - Catalyst ABC + NaOH (without water)> The same depolymerization reaction procedure was used as described in Example 10, using 0.034 g of iron-based ABC catalyst complex and 0.05 g of NaOH. After 240 min at 197° C., the reaction was stopped by cooling to below 160° C. The reaction mixture was transferred to a beaker through a sieve filter to remove remaining solids. The mixture was mixed. A pre-centrifugation sample was taken. The mixture was transferred to a centrifuge tube and centrifuged at 4000 rpm for 3 min. A post-centrifugation sample was taken. The sample was analyzed by XRF to estimate the separability. The results are shown in Figure 4.
[0080] <Example 13: Separation efficiency - Catalyst ABC + KOH (without water)> The same depolymerization reaction procedure was used as described in Example 10, using 0.034 g of iron-based ABC catalyst complex and 0.05 g of KOH. After 240 min at 197° C., the reaction was stopped by cooling to below 160° C. The reaction mixture was transferred to a beaker through a sieve filter to remove remaining solids. The mixture was mixed. A pre-centrifugation sample was taken. The mixture was transferred to a centrifuge tube and centrifuged at 4000 rpm for 3 min. A post-centrifugation sample was taken. The sample was analyzed by XRF to estimate the separability. The results are shown in Figure 4.
[0081] <Comparative Example D: Catalyst ABC> The depolymerization test was carried out using a 600 ml stainless steel high pressure reactor. 0.4 g of the iron-based ABC catalyst complex was added to polyethylene terephthalate (PET) flakes (0.1 × 0.02 cm 2 The reactor was placed in a heating device. Heating was started and after 25 minutes the reaction mixture reached a reaction temperature of 210°C. After 240 minutes at 210°C the reaction was stopped by cooling to below 160°C. The reaction mixture was transferred to a beaker through a sieve filter to remove remaining solids. Water was added to obtain a water:EG ratio of 0.8:1. The mixture was mixed. A sample was taken before centrifugation. The mixture was transferred to a centrifuge tube and centrifuged at 4000 rpm for 3 minutes. A sample was taken after centrifugation. The sample was analyzed by XRF to estimate the separation. Figure 1 shows the separation efficiency.
[0082] <Example 14: Catalyst ABC+NaOH> The same depolymerization reaction procedure was used as described in Comparative Example D, using 0.4 g of iron-based ABC catalyst complex and 0.6 g of NaOH. Figure 5 shows the separation efficiency obtained in Comparative Example D and Example 14. It was found that the addition of NaOH dramatically improved the separation efficiency of ABC catalyst, even at a high reaction temperature of 210°C.
Claims
1. A method for obtaining a monomer by decomposing a polymer, said polymer being a homopolymer or copolymer of said monomer, said method comprising the steps of: a) feeding the polymer and a solvent into a reactor as a reaction mixture, the solvent being a reactant capable of reacting with the polymer to break it down into oligomers and at least one monomer; b. providing a reusable catalyst capable of degrading said polymer into oligomers and at least one monomer; c. decomposing the polymer in the reaction mixture under reaction conditions using the catalyst to form at least one monomer; and d. Recovering the catalyst from the reaction mixture. and further comprising adding at least one base to the reaction mixture in at least one of the reaction steps a-d.
2. 10. The process of claim 1, wherein water is added to the reaction mixture before or during recovery of the catalyst.
3. 3. The process of claim 2, wherein water is added to the reaction mixture in an amount such that the mass ratio of water to solvent is in the range of from 0.2 to 5.0, preferably from 0.5 to 1.5, more preferably from 0.7 to 1.3, even more preferably from 0.9 to 1.
1.
4. 4. The process according to claim 2 or 3, wherein the base is added to the reaction mixture in an amount such that the mass ratio of base to water ranges from 0.01 to 1.0, preferably from 0.05 to 0.5, more preferably from 0.08 to 0.
12.
5. A process according to any one of claims 1 to 4, wherein the amount of catalyst relative to the amount of polymer ranges from 0.001:10 to 1:10, preferably from 0.005:10 to 0.3:10, more preferably from 0.008 to 0.015:
10.
6. 6. The process according to claim 5, wherein the base is added to the reaction mixture in an amount such that the amount of base to the amount of catalyst ranges from 0.1:1 to 40:1, preferably from 1:1 to 35:1, more preferably from 2:1 to 5:
1.
7. The process of any one of claims 1 to 6, wherein the base is a volatile base comprising an aqueous solution of ammonia and / or a trialkylamine.
8. The method according to any one of claims 1 to 6, wherein the base is a non-volatile base comprising a metal hydroxide.
9. Metal hydroxides include lithium hydroxide (LiOH), sodium hydroxide (NaOH), potassium hydroxide (KOH), rubidium hydroxide (RbOH), cesium hydroxide (CsOH), magnesium hydroxide (Mg(OH)), calcium hydroxide (Ca(OH)), strontium hydroxide (Sr(OH)), barium hydroxide (Ba(OH)), tetramethylammonium hydroxide (N(CH 3 ) 4 OH), and guanidine (HNC(NH 2 ) 2 9. The method of claim 8, comprising at least one of the following:
10. The method according to any one of claims 7 to 9, wherein a base is added in step a or step b.
11. 3. The process of claim 2, wherein water is added to the reaction mixture prior to recovering the catalyst in step d.
12. The process according to any one of claims 1 to 11, wherein after the decomposition step the reaction mixture is cooled to below 170°C.
13. 3. The process according to claim 2, wherein the addition of water to the reaction mixture before or during the recovery of the catalyst in step d is carried out at a temperature below 160° C., preferably below 100° C.
14. A process according to any one of claims 1 to 13, wherein the base is added in an amount to raise the pH of the reaction mixture to above 6.
15. A process according to any one of claims 1 to 14, wherein the recovery step comprises separating the catalyst from the reaction mixture.
16. 16. The method of claim 15, wherein the separating step is carried out using a centrifuge.
17. 16. The method of claim 15, wherein the separation step is performed using magnetic separation and / or application of an electric field.
18. A process according to any one of claims 15 to 17, wherein the separation is carried out at a temperature between 60°C and 100°C, preferably between 75°C and 95°C.
19. 19. The method of any one of claims 1 to 18, wherein the reusable catalyst comprises a catalytic complex comprising a catalytic entity, a metal-containing nanoparticle, and a bridging moiety binding the catalytic entity to the magnetic nanoparticle, the catalytic entity comprising a cationic moiety having a positive charge and an anionic moiety having a negative charge, preferably providing a negative counter ion.
20. A process according to any one of the preceding claims, wherein the weight ratio of the solvent, preferably ethylene glycol, to the polymer ranges from 20:10 to 100:10, more preferably from 40:10 to 90:10, most preferably from 60:10 to 80:
10.
21. The process according to any one of the preceding claims, wherein the polymer concentration in the dispersion is from 1 to 30% by weight of the total weight of the reaction mixture.
22. 22. The process according to any one of the preceding claims, wherein the decomposition step c) comprises forming the monomer at a temperature higher than 170°C, preferably up to 250°C, and at a pressure higher than 1.0 bar, preferably lower than 3.0 bar.
23. 10. Use of a base as defined in any one of claims 7 to 9 as a cocatalyst for a catalyst which decomposes a polymer in a reaction mixture under reaction conditions.
24. 24. The use according to claim 23, wherein the base is a fixed base.
25. 25. Use according to claim 23 or 24 as a cocatalyst for a catalyst as defined in claim 19.
Citation Information
Patent Citations
Methods and materials for depolymerizing polyesters
WO2015056377A1
Polymer degradation
WO2016105200A1
Improved catalyst complex and method of degradation of a polymer material
WO2017111602A1